Measuring the implementation of the rule of law in society and the state - K. K. Rakytianska (Bulletin of Kharkiv National University of Internal Affairs)
The subject of the research conducted in the article is the forms of measuring the rule of law in society and in the state. The purpose of the study is a comprehensive analysis of various forms of measuring the rule of law in society in order to identify areas for further improvement of implementing the rule of law in various aspects of public life. In the process of working on the research, various methods of scientific cognition were used, taking into account the goal, objectives of the research, its object and subject, namely: dialectical method, comparative method, structural logic method, method of system analysis. During the study a methodology for measuring the rule of law was developed, which is based on measuring the level of implementation of individual components, which together reflect the content of the rule of law. Such a comprehensive approach to the analysis of forms of measuring the rule of law is reflected for the first time in the scientific community. The article identifies the features of measuring the rule of law in Ukrainian society in view of the existing narrow conceptual reproduction of the principle of the rule of law in national law. It is concluded that one of the necessary favorable factors that is essential for the implementation of the rule of law is a democratic political regime. The possibility of measuring the rule of law in society through the prism of the overall goal to which it is aimed and through its functional purpose has been analyzed. It is established that in view of the new challenges caused by globalization and trends of deregulation, the implementation of the rule of law should be expanded. Proposals have been formulated on the need to expand the essence of the rule of law in the future as a guiding principle of organization of life so as to cover not only the relationship of the state with private entities, but also the activities of private entities whose opportunities to violate personal rights are the same as state power. The conclusions developed in the article can be used in law-making, law enforcement activities, as well as create a basis for further research in this area.